Freestanding borophene and Its hybrids - Ranjan, Pranay; Sahu, Tumesh Kumar; Bhushan, Rebti; Yamijala, Sharma S. R. K. C.; Late, Dattatray J; Kumar, Prashant; Vinu, Ajayan (Advanced Materials, 2019)
Borophene, an elemental metallic Dirac material is predicted to have unprecedented mechanical and electronic character. Need of substrate and ultrahigh vacuum conditions for deposition of borophene restricts its large-scale applications and significantly hampers the advancement of research on borophene. Herein, a facile and large-scale synthesis of freestanding atomic sheets of borophene through a novel liquid-phase exfoliation and the reduction of borophene oxide is demonstrated. Electron microscopy confirms the presence of beta(12), X-3, and their intermediate phases of borophene; X-ray photoelectron spectroscopy, and scanning tunneling microscopy, corroborated with density functional theory band structure calculations, validate the phase purity and the metallic nature. Borophene with excellent anchoring capabilities is used for sensing of light, gas, molecules, and strain. Hybrids of borophene as well as that of reduced borophene oxide with other 2D materials are synthesized, and the predicted superior performance in energy storage is explored. The specific capacity of borophene oxide is observed to be approximate to 4941 mAh g(-1), which significantly exceeds that of existing 2D materials and their hybrids. These freestanding borophene materials and their hybrids will create a huge breakthrough in the field of 2D materials and could help to develop future generations of devices and emerging applications.